Characterization of beta-lactam-resistant Escherichia coli from Australian fruit bats indicates anthropogenic origins. Issue 5 (5th May 2021) - McDougall, Fiona K.; Boardman, Wayne S. J.; Power, Michelle L.
Abstract : Antimicrobial-resistant Escherichia coli, particularly those resistant to critically important antimicrobials, are increasingly reported in wildlife. The dissemination of antimicrobial-resistant bacteria to wildlife indicates the far-reaching impact of selective pressures imposed by humans on bacteria through misuse of antimicrobials. The grey-headed flying fox (GHFF; Pteropus poliocephalus ), a fruit bat endemic to eastern Australia, commonly inhabits urban environments and encounters human microbial pollution. To determine if GHFF have acquired human-associated bacteria, faecal samples from wild GHFF ( n= 287) and captive GHFF undergoing rehabilitation following illness or injury ( n= 31) were cultured to detect beta-lactam-resistant E. coli . Antimicrobial susceptibility testing, PCR and whole genome sequencing were used to determine phenotypic and genotypic antimicrobial resistance profiles, strain type and virulence factor profiles. Overall, 3.8 % of GHFF carried amoxicillin-resistant E. coli (wild 3.5 % and captive 6.5 %), with 38.5 % of the 13 GHFF E. coli isolates exhibiting multidrug resistance. Carbapenem ( bla NDM-5 ) and fluoroquinolone resistance were detected in one E. coli isolate, and two isolates were resistant to third-generation cephalosporins ( bla CTX-M-27 and ampC ). Resistance to tetracycline and trimethoprim plus sulfamethoxazole were detected in 69.2% and 30.8 % of isolates respectively. Class 1 integrons, a genetic determinant of resistance, were detected in 38.5 % of isolates. Nine of the GHFF isolates (69.2 %) harboured extraintestinal virulence factors. Phylogenetic analysis placed the 13 GHFF isolates in lineages associated with humans and/or domestic animals. Three isolates were human-associated extraintestinal pathogenic E. coli (ST10 O89:H9, ST73 and ST394) and seven isolates belonged to lineages associated with extraintestinal disease in both humans and domestic animals (ST88, ST117, ST131, ST155 complex, ST398 and ST1850). This study provides evidence of anthropogenic multidrug-resistant and pathogenic E. coli transmission to wildlife, further demonstrating the necessity for incorporating wildlife surveillance within the One Health approach to managing antimicrobial resistance.